2010
DOI: 10.1021/ja100938r
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Universal “Adhesive Nanosheet” for the Assembly of Multiple Nanoparticles Based on a Protein-Induced Reduction/Decoration of Graphene Oxide

Abstract: Graphene oxide (GO) can be reduced and decorated by bovine serum albumin (BSA) at suitable pH and temperature. The resulting bioconjugates between BSA and GO or reduced GO are ideal templates for highly efficient assembly of a variety of nanoparticles with dramatically different compositions, sizes, shapes, and properties. This methodology offers a great chance for investigations on the structure-performance relationship of hybrid nanomaterials toward combinatorial material design aiming at special functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
545
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 800 publications
(567 citation statements)
references
References 49 publications
8
545
1
3
Order By: Relevance
“…By searching the literature, we found that many other nanoparticles produced wrinkles on GO as well. 13,[30][31][32][33][34] Our own experiment also indicated that silica nanoparticles can produce very obvious wrinkling ( Figure S2A). On the other hand, if GO is dried by itself, no extensive wrinkling was observed ( Figure 2F).…”
mentioning
confidence: 69%
“…By searching the literature, we found that many other nanoparticles produced wrinkles on GO as well. 13,[30][31][32][33][34] Our own experiment also indicated that silica nanoparticles can produce very obvious wrinkling ( Figure S2A). On the other hand, if GO is dried by itself, no extensive wrinkling was observed ( Figure 2F).…”
mentioning
confidence: 69%
“…Inorganic nanoparticles can assemble on the CMG surfaces as particle nucleated/anchored on CMG substrates, with different characters and morphologies, resulting in hybrid structures with unique features inherited not only from the individual components but also emerged from the synergistic coupling of their components 96, 97, 98, 99, 100. The inherent properties of graphene or chemically modified graphene make it a suitable substrate for nanomaterials in many various applications 101, 102.…”
Section: Self‐assembled Graphene‐based Hybrid Structuresmentioning
confidence: 99%
“…AuNPs can be decorated to GO surface based on NH-Au binding [108] or SH-Au binding [109]. DNA [110] and proteins [111] have been also used as the molecular linkers between AuNPs and GO. These methods have greatly increased the uniformity and density of AuNPs.…”
Section: Biomoleculesmentioning
confidence: 99%